2006
DOI: 10.1080/10803548.2006.11076700
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Workload of Underground Trammers in the Ranigang Coal Field Area of West Bengal, India

Abstract: physiological workload underground trammer coal mine aerobic capacityThe authors are grateful to the managerial authorities of various mines of Eastern Coalfield for providing necessary facilities for conducting this study. The authors also express their gratitude to the miners who volunteered for the study against various odds.Correspondence and requests for offprints should be sent to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
2
4
0
Order By: Relevance
“…The trend of recovery heart rate at the end of 1 st minute also indicated that the job would cause excessive cardiovascular strain if continued for the subjects. 14 Heart rates as found in the present study showed higher values than that of Bulgarian open cast blasters, diggers and drillers (100-110 beats/ min) 15 , Spanish underground coal face miners (103-106.5 beats/min) 16 , Australian miners (101-103 beats/min) 10 and Indian underground coal mine trammers (102-105 beats/min) 17 but lower from native underground coal mine carriers (124-133 beats/min) 18 and shovellers (130-138 beats/min) 19 and nearly comparable with the drillers (117-132 beats/min). 20 The higher level of RCC in dressers (44%-58%) can be explained from their significantly lower heart rate reserve level in relation to younger workers when compared with the Spanish underground miners (32%) 16 but lower from their native carrier (50%-66%) and shoveller counterparts (54% -65%).…”
Section: Discussionsupporting
confidence: 48%
“…The trend of recovery heart rate at the end of 1 st minute also indicated that the job would cause excessive cardiovascular strain if continued for the subjects. 14 Heart rates as found in the present study showed higher values than that of Bulgarian open cast blasters, diggers and drillers (100-110 beats/ min) 15 , Spanish underground coal face miners (103-106.5 beats/min) 16 , Australian miners (101-103 beats/min) 10 and Indian underground coal mine trammers (102-105 beats/min) 17 but lower from native underground coal mine carriers (124-133 beats/min) 18 and shovellers (130-138 beats/min) 19 and nearly comparable with the drillers (117-132 beats/min). 20 The higher level of RCC in dressers (44%-58%) can be explained from their significantly lower heart rate reserve level in relation to younger workers when compared with the Spanish underground miners (32%) 16 but lower from their native carrier (50%-66%) and shoveller counterparts (54% -65%).…”
Section: Discussionsupporting
confidence: 48%
“…A comparison with overseas results indicates that drillers in the present study had higher heart rates than those of Bulgarian open cast blasters, diggers and drillers (100-110 beats/min) engaged in extra repair activities 14) , Spanish underground coal face miners (103-106.5 beats/ min) 15) , Australian miners (101-103 beats/min) 9) and Indian underground coal mine trammers (102-105 beats/ min) 16) , but lower heart rates than native underground coal shovellers (130-138 beats/min) 17) . The peak values found in the older group (139 beats/min) and the younger group (135 and 145 beats/min) in both the spells (Figs.…”
Section: Comparative Aspects With Other Mining and Non-mining Occupatsupporting
confidence: 43%
“…humidity and high temperature are important and currently under research prerogative of many scientists. Meanwhile, different research studies have been documented some adverse effect of working environment on miner's cardiac and physiological stress (Dey et al, 2006, Dey et al, 2014. Not in India only, the same is also found in abroad countries (Hull et al, 1996), where high temperature and excessive humidity is found important thermal stress factors in underground mines.…”
Section: Introductionmentioning
confidence: 99%